2004
DOI: 10.1088/0953-8984/16/8/013
|View full text |Cite
|
Sign up to set email alerts
|

EPR of Sm3+in BaFCl single crystals

Abstract: BaFCl single crystals doped with Sm 3+ ions were studied by using the EPR method. Several types of paramagnetic Sm 3+ centres were found. The parameters of the corresponding spin Hamiltonians were determined. Structural models and ground states of the observed centres are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…In most cases, the average gvalue is close to 0.6. 32 As seen in the Fig. 2, the non-interacting limit describes the data at 8 K rather well.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…In most cases, the average gvalue is close to 0.6. 32 As seen in the Fig. 2, the non-interacting limit describes the data at 8 K rather well.…”
Section: Resultsmentioning
confidence: 58%
“…In agreement with the field-dependence observed for the magnetic specific heat, we have adopted a powder g Sm value of 0.6, which is in the range observed for Sm(III) in sites of low-symmetry. 32 The ground multiplet of Sm(III), 6 H 5/2 , is split by a cubic crystal field into a doublet C 7 and a quartet C 8 . 33 In crystal fields of lower symmetry, the quartet C 8 splits into two Kramer doublets C 6 and C 7 .…”
Section: Resultsmentioning
confidence: 99%
“…9 and 10. Clear angular dependence for the monoclinic Sm 3+ in ab and ac * planes are observed [12]. Different lines (8+8) belonging to 145 and 147 isotopes of samarium are visible.…”
Section: Epr Properties Of Ksw Single Crystalmentioning
confidence: 81%
“…2) and may be attributed to an oxygen impurity related defect. Oxygen is a common impurity in barium fluorohalides (Falin et al, 2004) and typically forms two types of oxygen-vacancy centers. In BaFCl, the type I defect complex consists of oxygen substituted for a fluorine ion with a neighboring chlorine vacancy.…”
Section: Resultsmentioning
confidence: 99%
“…3). EPR studies of BaFCl single crystals conventionally doped with Sm have also found that Sm 3+ is the dominant ion species, and most probably substitutes for Ba 2+ with charge compensation provided by an O 2− ion, which substitutes for a nearby Cl − ion in the BaFCl host lattice (Falin et al, 2004).…”
Section: Resultsmentioning
confidence: 99%